Facile mechanochemical modification of g-C3N4 for selective photo-oxidation of benzyl alcohol. (2nd February 2019) - Cerdan, Kenneth; Ouyang, Weiyi; Colmenares, Juan C.; Muñoz-Batista, Mario J.; Luque, Rafael; Balu, Alina M.
Graphical abstract: Highlights: Facile mechanochemical synthesis of g-C3 N4 -ZnO and -Fe2 O3 composite photocatalyts. Maximum benzaldehyde selectivity (70%) for the g-C3 N4 -Fe2 O3 composite sample. Crystallinity and surface concentration of the oxides control the selectivity of benzyl alcohol oxidation. Abstract: Graphitic carbon nitride (CN) enriched with ZnO or Fe2 O3 were synthesized using a simple one-pot mechanochemical method. By using this method, composite samples were synthetized without the production of any potentially hazardous waste. Synthesized materials were used as catalysts during selective photo-oxidation of benzyl alcohol. Both composite materials displayed an enhancement of activity and benzaldehyde selectivity with respect to the pure CN. The most active catalyst was Fe2 O3 /g-C3 N4 (Fe/CN). Conversion and benzaldehyde selectivity of this sample were 20 and 70%, respectively. It showed a considerable increase of benzaldehyde selectivity compared to the pure CN and TiO2 P25 commercial reference. A complete structural and electronic characterization using Scanning Electron Microscopy-Energy Dispersive (SEM-EDX), BET measurements, X-ray diffraction (XRD), X-ray Photoelectron (XPS), and UV–visible spectroscopies was carried out. The characterization analysis pointed out the leading role of the crystallinity and surface concentration over the activity and benzaldehyde selectivity of the reaction.